2014
DOI: 10.1007/s40258-014-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Costs of Opioid Abuse and Dependence from an Employer Perspective: a Retrospective Analysis Using Administrative Claims Data

Abstract: BackgroundOpioid abuse and dependence is problematic across many age groups, including the working-age population and their dependents. Little is known, however, about the economic costs of opioid abuse/dependence imposed on employers, who pay for a substantial portion of healthcare costs through their contributions to employer-sponsored health insurance and are also affected by indirect costs such as those due to disability and workplace absenteeism.ObjectiveTo provide a comprehensive, current estimate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 15 publications
(21 reference statements)
3
70
3
Order By: Relevance
“…A final group of 16 publications were selected for inclusion in the report. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The two primary reasons for exclusion were an abuse treatment focus (15) and lack of cost data (12). A CASP checklist was completed for these 16 publications to assess quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A final group of 16 publications were selected for inclusion in the report. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The two primary reasons for exclusion were an abuse treatment focus (15) and lack of cost data (12). A CASP checklist was completed for these 16 publications to assess quality.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies directly compared the health care costs of patients who were opioid abusers with those of a control population of patients who were not opioid abusers. 9,12,[15][16][17][18]20,23 In each of these studies, opioid abuse was identified by medical claims submitted with a diagnosis code for opioid abuse, dependence, or poisoning. Pasquale et al 16 and White et al 23 dealt with more than one payer type, including both commercial insurance and Medicaid or Medicare.…”
Section: Payer Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This study built upon a recently published paper on the costs of opioid abuse from an employer perspective 6 . Specifically, we used the same sample of patients, aged 12-64, diagnosed with opioid abuse or dependence ('abusers') as well as a sample of those not diagnosed with opioid abuse or dependence ('non-abusers') from the de-identified OptumHealth Reporting and Insights (OptumHealth) medical and pharmacy claims database, Q1 1999-Q1 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were required to have continuous eligibility over an 18 month study period surrounding the first abuse diagnosis. Details of the study period and inclusion criteria are described in Rice et al 6 . To estimate the potential extent of diversion, we examined what share of abusers had access to prescription opioids through prescriptions they obtained prior to their index date, defined as the date of their first abuse diagnosis.…”
Section: Methodsmentioning
confidence: 99%